Work motivation and values in Argentine volunteer and paid firefighters - Piedimonte, Florencia Rocío (2018)
The Fire Department is a protection force for the citizens of a country. Because of its role and function, it is of vital importance to the community. This study investigates the relationship between Motivation, conceptualized as a guiding variable of behavior, and Work Values, considered as guides in the career of firefighters of the Autonomous City of Buenos Aires (Argentina). A descriptive, correlational and group difference study was carried out with a sample of 130 firefighters (25 women and 105 men), of whom 67 were paid and 63 were volunteers. The average age was 32.32 years. The Work Motivation Scale (adapted to Spanish by Gagné et al., 2012) and the Revised Scale of Work Values by Porto and Pilati (2010, Argentine adaptation by Moreno and Marcaccio, 2012) were used. It was found that extrinsically-motivated firefighters confer, autonomously and deliberately, significance to their actions based on values such as personal achievement, self-perceived competence and, above all, social utility (i.e. Altruism). Consequently, their work complies with their expectations of personal well-being and, at the same time, is aimed at improving the life of their social peers.